Respiratory Syncytial Virus Infection of the Newborn. Issue 5715 (18th July 1970) - Neligan, G. A.; Steiner, H.; Gardner, P. S.; McQuillin, J.
Abstract : In an outbreak of respiratory syncytial (R.S.) virus infection in a maternity hospital the respiratory illness was of a mild nature and the virus was not found in infants without respiratory symptoms. This confirms the suggestion that R.S. virus can infect infants at a very early age. Rapid diagnosis was achieved by applying the direct fluorescent antibody technique to cells in nasal secretions. This proved to be more sensitive than culture techniques where there was delay between the onset of respiratory symptoms and submission of specimens to the laboratory.